Efectos del bicarbonato sodico sobre la acidosis lactica y el rendimiento en pruebas sucesivas de 300 m - Garcia Caicoya, A. M. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2003)
This study aims to test the effect of the ingestion of Sodium Bicarbonate (NaHCO3) on athletic performance. Ten high level athletes ingested 300mg/kg of sodium bicarbonate one hour before the tests. Following this on two different occasions which were six days apart, they ran repeated series of 300 metres between 80-83% of the best time at this distance until they were exhausted or performance fell below these percentages. The participants were randomly divided into two groups and were given the sodium bicarbonate mixed with fruit juice in order to conceal the taste. On one of the test days they carried out the tests having ingested sodium bicarbonate with the fruit juice, whilst the other day they didn`t have anything. The results of the two tests have highlighted significant differences, showing that the participants were able to complete a greater series of 300 metres having taken the sodium bicarbonate than without it. Based on the results obtained, it is possible to suggest that sodium bicarbonate could be used in training programmes to help achieve greater metabolic changes.